Manifestation of the effect of heterosis on the productive characters of pigs - Grishina, L.; Onyshchenko, A.; Krasnoshchok, O. (Scientific Progress & Innovations, 2022)
One of the tasks for the domestic pig industry is to improve the breeding traits of pigs in order to increase meat production. First of all, it is necessary not only to increase the volume of production obtained, but also to minimise labour and costs, making it competitive on the world market. Scientific research proves the feasibility of using crossbreeding and hybridization methods to increase the productive traits of animals by ensuring the effect of heterosis. To obtain marketable pigs, effective options for combining breeds in terms of productivity and growth intensity of young animals in early ontogeny are proposed. The aim of the research is to determine the effect of heterosis on reproductive and fattening qualities of purebred, crossbred and hybrid pigs under intensive technologies depending on the growth intensity of young animals in early ontogeny. According to the data of dispersion analysis a significant influence of boars-producers on the indicator of prolificacy and the litter’s weight at birth of 61.13 % and 59.37 % respectively. Producers also have an influence on the multiple birth rate (27.1 %), number of newborn piglets (39.9 %) and birth weight (59.4 %). Other reproductive traits such as a litter’s weight and number of piglets at weaning as well as piglet survival are more influenced by paratypical factors than genotypical ones. The effect of normal heterosis in the VB×L and hypothetical heterosis in the (VB×L)×(D×H) combinations has been determined for prolificacy of sows. According to the index of the litter’s weight at birth, the VB×L and (VB×L)×(L×H) combinations showed positive overdominance (7.33 and 2.67 units, respectively), while the VB×L(L×H) combination showed intermediate dominance. As a result of studies to determine the effect of heterosis, true heterosis in terms of "average daily gain" and "feed consumption" was found only in pigs of the VB×L combination of the plus-variant class. Normal heterosis in the indicator "age of reaching 100 kg body weight" was ascertained for pigs of all experimental groups, in the traits "average daily gain" and "feed consumption" - in combinations of VB×L and VB×(D×H) of the plus- and minus-variant class and hybrids of the plus-variant class. Hypothetical heterosis was determined in animals of the VB×L plus- and minus-variant combinations according to "age at 100 kg live weight" and "feed consumption", and in "average daily gain" – in pigs of the VB×L and VB×(D×H) plus- and minus-variant combinations.